2021
DOI: 10.1038/s41598-021-01210-9
|View full text |Cite
|
Sign up to set email alerts
|

Lack of affective priming indicates attitude-behaviour discrepancy for COVID-19 affiliated words

Abstract: The ongoing novel coronavirus (COVID-19) pandemic has resulted in the enforcement of national public health safety measures including precautionary behaviours such as border closures, movement restrictions, total or partial lockdowns, social distancing, and face mask mandates in order to reduce the spread of this disease. The current study uses affective priming, an indirect behavioural measure of implicit attitude, to evaluate COVID-19 attitudes. Explicitly, participants rated their overall risk perception as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…We tentatively suggest that the representation of emotional features is dynamic, so that new affective experiences linked to these COVIDrelated concepts may progressively modify their semantic representations reverting them to their pre-pandemic baselines. Of note, a recent study has revealed a dissociation between the explicit assessment of word emotional features and the implicit representation of these properties (Moro & Steeves, 2021). Thus, although participants in their study rated as unpleasant different COVID-related words, no affective priming effect (a marker of implicit attitudes) was observed for this type of words, revealing a lack of interiorization of COVID-related notions.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…We tentatively suggest that the representation of emotional features is dynamic, so that new affective experiences linked to these COVIDrelated concepts may progressively modify their semantic representations reverting them to their pre-pandemic baselines. Of note, a recent study has revealed a dissociation between the explicit assessment of word emotional features and the implicit representation of these properties (Moro & Steeves, 2021). Thus, although participants in their study rated as unpleasant different COVID-related words, no affective priming effect (a marker of implicit attitudes) was observed for this type of words, revealing a lack of interiorization of COVID-related notions.…”
Section: Discussionmentioning
confidence: 58%
“…Keep in mind that words constitute the main and more essential pieces of communication (i.e., they are like cells for biologists). In this regard, a recent study that studied implicit COVID-19 behaviors using affective priming techniques showed that, although individuals consciously rated COVID-related words as unpleasant, no affective priming effect was observed with these lexical units (Moro & Steeves, 2021). This effect could be explained in terms of lack of changes in the representation of the emotional features of the unpleasant COVIDrelated meanings despite the explicit rating of these words as unpleasant, thus showing on the one hand a differential processing and evaluation of words that allude to emotional aspects of the pandemic, and a potentially unaltered implicit representation, on the other hand.…”
Section: Introductionmentioning
confidence: 99%
“…We predicted that pro-vaccination participants will explicitly rate their risk perception associated with contracting COVID-19 significantly higher compared to vaccine-hesitant participants. Further, similar to Moro and Steeves (2021) we predicted that all participants would classify COVID-19 associated words as unpleasant during baseline trials. Finally, despite classifying COVID-19 associated words as being unpleasant, we predicted that on one hand, pro-vaccination participants would demonstrate affective priming, therefore indicating that their explicit and implicit attitudes towards COVID-19 are aligned, whereas on the other hand, vaccine-hesitant participants would not show affective priming demonstrating an attitude-behaviour discrepancy.…”
supporting
confidence: 60%
“…Stimuli were made up of words from three affect categories: pleasant, unpleasant, and COVID-19. All stimuli were the same as those used in Moro and Steeves (2021). Briefly, on each trial the affective valence of the prime and the target was either congruent or incongruent.…”
Section: Stimulimentioning
confidence: 99%
“…In small towns with small populations, like Gerash, a negative attitude to social distancing and home quarantine can lead to new local waves of infection. Stefania S Moro (2021) reported that a negative attitude toward social distancing paves the way for the faster spread of COVID-19 [30]. Cephas Sialubanje et al (2022) found that future interventions in the domain of COVID-19 prevention should be based on correcting people's attitude to and observance of social distancing [31].…”
Section: Discussionmentioning
confidence: 99%